(untitled) (Research, Society and Development, 2021)
This research presents school management and how it promotes reception in the teaching unit, in view of the presence of students who need special care. The school manager or principal is responsible for keeping the entire school in good working order, as well as for the plans that guide academic activities, enabling the school community to experience new challenges and learning. It is worth remembering that a democratic management must provide a clear work involving the active participation of other individuals, for this, it is necessary that the school is open to new changes such as enabling the inclusion of students with special needs, providing all educational support accordingly. with the law. This study had the problem of understanding the role of the manager regarding the inclusion of students with special needs in the school environment. And for this inclusion process to happen, it is of paramount importance for the family to also be inserted in the environment to monitor the development of learning, then the manager comes to adapt to the environment, teaching materials, resource room, and regular room to teachers and caregivers, and especially to the school environment, which is where education is promoted, training professionals for the labor market.